Plant cell wall and the mechanisms of resistance to pathogens - O. G. Smirnova; A. V. Kochetov (Вавиловский журнал генетики и селекции)
A huge variety of phytopathogens (viruses, bacteria, fungi) are potentially able to infect plant tissues and cause diseases. Numerous plant genes control a complex network of defense mechanisms based on both constitutive and inducible processes. The cell wall is a primary barrier the pathogens have to penetrate to start the infection process. However,it is able to block invasion by most non-specific potential pathogens. The cell wall structure may differ in various plant species. It is based on the net of cellulose microfibrils linked by hemicellulose molecules. Pectin and lignin are the other important cell wall constituents. Dozens of proteins inside the cell wall are involved in structural and metabolic processes as well as in signal transduction and regulatory circuits (more information is available in W allProtDB database). Each of these components contributes to resistance to pathogens. At the points of contact with potential pathogens cell wall structural changes and accumulation of metabolites with antimicrobial, antifungal or antiviral activities occur. Some pathogens could produce hydrolytic enzymes able to degrade cellulose and pectin to counteract these non-specific plant resistance mechanisms. In turn, plants developed the inhibitors of pathogen-related enzymes and this “arms race” is an important part of plant evolution and host-pathogen interaction mechanisms. Plants also can evaluate the cell wall state to compensate for imbalances and deficiencies. For instance, mutants with cellulose deficiency may have a higher lignification rate and a stronger stress response. The cell wall is also a source of signal molecules triggering the initiation of response mechanisms. In total, the plan cell wall is a complex dynamic structure able to prevent infection by most potential (non-specific) pathogens and switch on the mechanisms of plant immune response. The reconstruction of gene networks controlling the cell wall structural and functional organization during the growth, and under normal and stressful conditions is vitally important for understanding the basic molecular mechanisms of development and stress resistance. The mechanisms of specific and non- specific plant resistance to various phytopathogens connected to the cell wall structure are reviewed. The roles of the cell wall constituents in pathogen detection and the induction of defense mechanism are discussed